Pengaruh Pelatihan Hand Only CPR pada Siswa SMK Kesehatan Dalam Penanganan Henti Jantung: The Effectivity of Hand Only CPR Training for Student of Health Vocational Schools in Handling Cardiac Arrest - Yundari, Anak Agung Istri Dalem Hana; Asdiwinata, I Nyoman (Bali Medika Jurnal, 2021)
Background: Out-of-Hospital Cardiac Arrest (OHCA) is a heart disorder condition that often threatens a person's life. Handling in this incident as much as 40.1% received Cardiac Pulmonary Resuscitation  (CPR) by people around the victim with the survival rate of victims who received CPR action at the location of the incident reaching 9.5%. Hand only CPR is the foundation to handling for cardiac arrest and as a fundamental aspect of Basic Life Support (BLS) by recognizing Sudden Cardiac Arrest (SCA), seeking emergency help, and immediate chest compressions that can be performed by common people. Health Vocational School students are part of ordinary people who at this level of education have not yet obtained competency in handling cardiac arrest through CPR. Purpose. The purpose of this study was to determine the effectiveness and effect of hand only CPR training on Health Vocational School students in the handling cardiac arrest. Methods: Quantitative correlation with bivariate pre-post design test without control through lecture and simulation methods using Cardiac Resuscitation (CPR) panthom. Results: Mac Nemar's analysis test: p = 0.000 (p <0.05) with the category most (24 people) had good skills after receiving Hand Only CPR training. Conclusion: There was a significant relationship before and after being givenhand only CPR training.